Synthetic Strategy Towards Heterodimetallic Half-Sandwich Complexes Based on a Symmetric Ditopic Ligand - Green, Lewis P. M.; Steel, Tasha R.; Riisom, Mie; Hanif, Muhammad; Söhnel, Tilo; Jamieson, Stephen M. F.; Wright, L. James; Crowley, James D.; Hartinger, Christian G. (Frontiers in Chemistry, 2021)
Multimetallic complexes have been shown in several examples to possess greater anticancer activity than their monometallic counterparts. The increased activity has been attributed to altered modes of action. We herein report the synthesis of a series of heterodimetallic compounds based on a ditopic ligand featuring 2-pyridylimine chelating motifs and organometallic half-sandwich moieties. The complexes were characterized by a combination of 1H NMR spectroscopy, electrospray ionization mass spectrometry, elemental analysis and single crystal X-ray diffraction. Investigations into the stability of representative complexes in DMSO-d6 and 10% DMSO-d6/D2O revealed the occurrence of solvent-chlorido ligand exchange. Proliferation assays in four human cancer cell lines showed that the Os-Rh complex possessed minimal activity, while all other complexes were inactive.